Meningkatkan Motivasi Mahasiswa dalam Reading Comprehension dengan Strategi Multiple Intelligences - A’am Rifaldi Khunaifi (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
The study discusses about improving students’ motivation on reading comprehension by using Multiple Intelligences strategies. The objectives of the study are explaining 1) the problems faced by the Students the first semester at UMP in reading comprehension, 2) the implementation of Multiple Intelligences strategies in motivating reading comprehension for the students the first semester at UMP, 3) how Multiple Intelligences strategies improve the motivation of the students the first semester at UMP. In order to achieve the objectives, the researcher held an action research at Muhammadiyah of University. There were 2 cycles in which 2 meetings held for each cycle. The subject of the study is the students the first semester at UMP. The numbers of population are 32 students. The instruments used were observation sheet, questionnaire, and CARI. The result of the study is the problem in motivating students to read. This can be solved by using Multiple Intelligences strategies which combine students’ intelligences with fun learning activities through Multiple Intelligence instructions. Based on the questionnaire, all of the students said that the strategies used were interesting. In line with the questionnaire result, the observation sheet also showed the excellent result of students’ study habits. There was an improvement on students’ comprehension, it can be seen from the mean of CARI I which was 89.06 point and CARI II which was 95.6 point. I suggest that the lectures should be able to use the Multiple Intelligences strategies as an alternative in motivating students and creating enjoyable learning experiences.